Gender and Music Composition: A Study of Music, and the Gendering of Meanings - Sergeant, Desmond C.; Himonides, Evangelos (Frontiers in Psychology, 2016)
In this study claims that music communicates gendered meanings are considered, and relevant literature is reviewed. We first discuss the nature of meaning in music, and how it is constructed and construed. Examples of statements of gendering in the literature are cited, and the problems identified by writers who have questioned their validity are considered. We examine the concepts underlying terminology that has been used in inconsistent and contradictory ways. Three hypotheses are posed, and tested by means of two listening tasks. Results are presented that indicate that gendering is not inherent in musical structures, but is contributed to the perceptual event by the listener.